Optimalisasi Penjadwalan Proyek Pembuatan Reactor Tank Dengan Menggunakan Critical Path Method - Muhammad Wibbie Wiweka Subono; Sumiati (Jurnal Serambi Engineering, 2025)
Project management itself is the process of combining tools, resources and techniques to achieve predetermined goals. If all activities are managed according to clear objectives and outcomes, the project will run according to plan. On-site project monitoring should be carried out regularly to predict possible errors in terms of time, cost, etc. The purpose of this study was to analyse the schedule, identify the critical path and compare the total labour costs in the manufacture of reactor tanks by PT. PDK. The approach used is the Critical Path Method (CPM) supported by POM-QM software. The study is descriptive with a quantitative approach. The conclusions are as follows: First, the activity schedule consists of 28 activities, with the activity sequence A-B-C-D-E-F-G-H-I-J-K-L-M-N-O-P-Q-R-S-T-U-V-W-X-Y-Z-AA-AB with a duration of 158 days; Second, the results of the CPM analysis show a pattern of activity paths, where the critical path of the reactor tank construction project is A-B-C-D-E-F-G-H-I-J-K-L-M-Z-AA-AB with a duration of 108 days; and thirdly, the application of the CPM method successfully reduced the labour cost of the project from Rp 97,960,000 to Rp 66,960,000, which means that there was a cost saving of Rp 31,000,000. The application of project management through CPM analysis shows that the project schedule and cost become more optimal, effective and efficient, and the results of this study are consistent with previous studies that discuss project management methods.